Freeing the Buddha. Diversity on a Sacred Path – Large Scale Concerns. By Vladimir Korobov - Ruhe, Brian (Acta Orientalia Vilnensia, 2005)
Center of Oriental Studies, Vilnius UniversityBRIAN RUHE. Freeing the Buddha. Diversity on a Sacred Path – Large Scale Concerns. A course on major aspects of Buddhism plus a dangerous collection of essays, Delhi: Motilal Banarsidass, 2005, xxiv, 477 pp. ISBN 81-208-1835-0, HC, Rs. 595